Report of the Working Group Eighth Five Year Plan 1990-95 Electronics Industry - Planning Commission (Planning Commission, 1989)
Electronics technology and industry have a tremendous potential for improving the standard of living and quality of life of people because of its versatility and easy adaptability, offering most appropriate technological choices suited to Indian conditions for solving many of the socio-economic problems and to achieve the objectives of growth and employment. Electronics also plays a dominant role in improving productivity in industry. Modern on-line process control instrumentation, data acquisition systems, appropriate automation of the production processes and computerised design can reduce down-time considerably, help fuller utilisation of existing capacities and improve industrial efficiency. Today, the safety in the air, on the ground, on the rails, on roads, on the high seas, in factories and mines, depends heavily on electronics technology.
Department of Electronics
Department of Electronics